Academic Supervision and Teachers’ Pedagogical Competencies: Their Impact on Learning Quality in Indonesian Primary Schools - Mekarsari, M Maya; Bunyamin; Sudana, I Made (Universitas Nahdatul Ulama Surabaya, 2025)
Quality education in primary schools faces persistent challenges, particularly regarding the role of academic supervision and pedagogical competencies in learning outcomes. This study aims to examine the individual and combined effects of academic supervision and teachers’ pedagogical competencies on learning quality in Indonesian primary schools. A quantitative survey using ex post facto correlational design was conducted with 110 primary school teachers from 10 schools in Gugus Bawana Ageng, Tembalang District, Semarang City, selected through proportionate random sampling. Data were collected using validated questionnaires and analyzed through descriptive statistics, correlation analysis, and multiple regression. Results reveal strong positive correlations between academic supervision and learning quality (r = 0.749) and pedagogical competence and learning quality (r = 0.619). Academic supervision contributed 56.1% to learning quality variance, while pedagogical competence contributed 38.3%. Combined, both variables explained 67.1% of learning quality variance (R2 = 0.671). The study concludes that academic supervision demonstrates stronger predictive power than pedagogical competence in determining learning quality. Implications suggest prioritizing structured supervisory systems and targeted teacher development programs. Future research should explore longitudinal relationships and investigate the remaining unexplained variance through mixed-methods approaches.